Three new species of European Coletinia Wygodzinsky (Zygentoma, Nicoletiidae), with additional records and an updated identification key - Molero-Baltanás, Rafael; Gaju-Ricart, Miquel; Fišer, Žiga; Bach de Roca, Carmen; Mendes, Luís F. (European Journal of Taxonomy, 2022)
We describe three new species of the genus Coletinia Wygodzinsky, 1980, the most diverse of the family Nicoletiidae (order Zygentoma = Thysanura s. str.) in Europe: C. dalmatica Molero-Baltanás, Fišer, Bach de Roca & Gaju-Ricart sp. nov. from Croatia, C. dextra Molero-Baltanás, Bach de Roca & Gaju-Ricart sp. nov. from Spain and C. serrata Mendes, Molero-Baltanás, Bach de Roca & Gaju-Ricart sp. nov. from Portugal. Coletinia dalmatica sp. nov. seems to be related with C. maggi (Grassi, 1887) and both Iberian species belong to the asymetrica species group. New material of some previously recognized species (C. diania Molero, Bach & Gaju, 2013, C. intermedia Molero, Bach & Gaju, 2013, C. mendesi Wygodzinsky, 1980, C. redetecta Molero, Bach & Gaju, 2013 and C. tinauti Molero-Baltanás, Gaju-Ricart & Bach de Roca, 1997) is reported, enlarging in most cases their geographic distribution, and including some new data on their intraspecific variability. Finally, an updated identification key to all known species of the genus Coletinia is given.